Challenges for CTC-based liquid biopsies: low CTC frequency and diagnostic leukapheresis as a potential solution. (1st February 2016) - Stoecklein, Nikolas H.; Fischer, Johannes C.; Niederacher, Dieter; Terstappen, Leon W. M. M.
ABSTRACT: Circulating tumor cells (CTCs) are very attractive surrogate markers for systemic cancer. Currently, major efforts are being made to use these rare cells in the sense of a liquid biopsy to gain molecular information for rational therapeutic decision-making. The advancements in molecular analyses of CTCs down to the single-cell level have been significant in recent years and some applications are ready to be used in clinical studies. As discussed in this review, a major challenge for translating such molecular CTC-based assays into the clinic is the extremely low frequency of CTCs and the associated problems of their reliable detection and isolation. A potential solution to overcome the low CTC frequency is the recently introduced diagnostic leukapheresis that permits screening of liters of blood. Discussed here are the challenges as well as the current efforts implementing this method into clinical workflows to realize more reliable liquid biopsies.